2010
DOI: 10.1103/physreve.81.041922
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of fluid vesicles with in-plane orientational ordering

Abstract: We present a method for simulating fluid vesicles with in-plane orientational ordering. The method involves computation of local curvature tensor and parallel transport of the orientational field on a randomly triangulated surface. It is shown that the model reproduces the known equilibrium conformation of fluid membranes and work well for a large range of bending rigidities. Introduction of nematic ordering leads to stiffening of the membrane. Nematic ordering can also result in anisotropic rigidity on the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
160
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(161 citation statements)
references
References 43 publications
1
160
0
Order By: Relevance
“…The principal directions and the local surface normal form a local orthonormal frame of reference (Darboux frame). The details of the calculation of the discrete shape operator are given in [35]. The discretised form of the Helfrich's free energy eq.…”
Section: Triangulated Surface Modelmentioning
confidence: 99%
“…The principal directions and the local surface normal form a local orthonormal frame of reference (Darboux frame). The details of the calculation of the discrete shape operator are given in [35]. The discretised form of the Helfrich's free energy eq.…”
Section: Triangulated Surface Modelmentioning
confidence: 99%
“…[22] It has been shown that the entropy dominated branched shapes, the equilibrium shapes of flexible surfaces(κ = 0), are cut off by order induced membrane stiffening. These observations add support to the hypothesis of membrane shape stabilization by protein-lipid interactions.…”
Section: Frustrated In-plane Order and Membrane Morphologymentioning
confidence: 99%
“…We will outline, in this article, the basic steps to compute these surface geometrical quantifiers. [22] Computing surface quantifiers…”
Section: In-plane Orientational Ordermentioning
confidence: 99%
See 2 more Smart Citations